The Interface Between South Asian Culture and Palliative Care for Children, Young People, and Families—a Discussion Paper. (March 2013) - Brown, Erica; Patel, Reena; Kaur, Jasveer; Coad, Jane
<x xml:space="preserve">Abstract</x> A fundamental element of quality healthcare is that provision is accessible to all users and culturally sensitive to them. However, there is evidence to suggest that there is inequity of provision across all cultures. Furthermore, there is a paucity of published research in the United Kingdom concerning palliative care for minority ethnic families with a life-threatened or life-limited child or young person. The article sets out to discuss the findings of a literature review and, drawing on current work by the Centre for Children and Families Applied Research at Coventry University under the leadership of Professor Jane Coad, to explore the interface between South Asian cultures and the experience of palliative care services of children, young peoples, and families. All families require a broad range of services which are appropriately delivered and accessible throughout the trajectory of their child's illness. The literature review findings reveal that how families understand concepts such as health and disease arise from the complex interaction between personal experience and cultural lifestyle including language, family values, and faith. There is an urgent need to involve South Asian families in research in order to provide a robust evidence-base on which to develop service provision so that care is matched to the unique needs of individuals concerned.